(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The abstract contains a brief description of the purpose: To find out the relationship between pre-match anxiety levels and the performance of court tennis players aged 12-18 years. This research uses a qualitative approach with a qualitative descriptive type. The population in this study is field tennis players aged 12-18 years in the Pekalongan Regency area, Central Java, who actively participate in competitions. Pre-match anxiety levels in the tennis players in this sample were mostly in the medium category, with a small percentage in the high and low categories. This study found interesting findings on how anxiety at this level interacts with perceived performance. The majority of players who experience "moderate" anxiety are still able to achieve "high" to "very high" performance. This indicates that for most of the athletes in this sample, anxiety, while significant, can serve as a trigger for arousal and alertness that supports optimal performance. The instrument used in this study was a questionnaire. The questionnaire distributed is the SCAT (Sport Competitive Anxiety Test) questionnaire. The instruments used to measure skills are service accuracy, forehand and backhand stroke tests, volley stroke tests, and rally tests.